2020
DOI: 10.1088/1361-665x/ab859e
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on shock control of a vehicle semi-active suspension with magneto-rheological damper

Abstract: During driving process, the impact from the road, such as pothole or bump can deteriorate the performance of the vehicle, and increase the driving dangerousness and health risk of drivers/passengers due to high energy and short time. The magneto-rheological (MR) intelligent suspension plays an important role in improving the ride comfort of vehicle, which can reduce the impact transmitted from the road. In consideration of different impact application induced by different driving speed, an adaptive skyhook con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…This advantage is currently only available at the price of using external power to provide the electromagnetic coils with the required electrical current [ 22 , 23 ]. Damping power in semi-active suspension uses from 5% to 30% of the total damping power to control the process [ 24 , 25 ]. The semi-active damping process creates the possibility of collecting energy from damping rather than simply dissipating it.…”
Section: Introductionmentioning
confidence: 99%
“…This advantage is currently only available at the price of using external power to provide the electromagnetic coils with the required electrical current [ 22 , 23 ]. Damping power in semi-active suspension uses from 5% to 30% of the total damping power to control the process [ 24 , 25 ]. The semi-active damping process creates the possibility of collecting energy from damping rather than simply dissipating it.…”
Section: Introductionmentioning
confidence: 99%
“…In Ma et al (2021), a new neuro-inverse model of the MR fluid damper based on the Elman neural network was established, and an optimized fuzzy skyhook controller with gray wolf optimizer algorithm was designed based on the inverse model to control the suspension system. In Du et al (2020), an adaptive skyhook controller based on an improved genetic algorithm was proposed, and the designed controller was verified by the road test for the vehicle installed with MR dampers.…”
Section: Introductionmentioning
confidence: 99%
“…It has great promise for semi-active vibration control [5], such as intelligent suspension damping for automobiles [6], and bridge and building damping [7]. Affected by the internal parameters of the damper and other factors, the dynamic response has a time delay and affects the control accuracy, and the damping performance of the system cannot be guaranteed [8]. After analyzing the dynamic characteristics of the MRD, it can be observed that the link from the driver drive voltage to the damper current has a great influence on the dynamic characteristics of the damper [9].…”
Section: Introductionmentioning
confidence: 99%